Use of lateral flow assays to determine IP-10 and CCL4 levels in pleural effusions and whole blood for TB diagnosis. (January 2016) - Sutherland, Jayne S.; Mendy, Joseph; Gindeh, Awa; Walzl, Gerhard; Togun, Toyin; Owolabi, Olumuyiwa; Donkor, Simon; Ota, Martin O.; Kon Fat, Elisa Tjon; Ottenhoff, Tom H.M.; Geluk, Annemieke; Corstjens, Paul L.A.M.
Summary: One of the key problems in combating TB is the lack of fast and accurate diagnostic tests that are affordable and easy to use in resource-limited settings. We have used a field-friendly up-converting phosphor (UCP) reporter technology in a lateral flow (LF) based test for the diagnosis of respiratory infections. In this study we analysed samples obtained from patients presenting with symptoms suggestive of TB but prior to confirmation by microbiology in The Gambia. Following clinical and microbiological evaluation they were classified as either having TB or other respiratory disorder (ORD). Analysis of blood was performed for those with pulmonary TB and pleural fluid for those with pleural TB. UCP-LF test for detection and quantitation of IP-10 and CCL4 were used being the two chemokine markers that have been shown to increase in active TB disease. UCP-LF test accurately determined concentrations of both markers as compared to ELISA and multiplex cytokine array. However, only IP-10 could discriminate between TB and ORD, and this was significantly enhanced by analysing the site of infection (pleural fluid), which showed 92% correct classification. Future work will assess the use of multiple markers to increase diagnostic accuracy.